Broadband Chirped InAs Quantum-Dot Superluminescent Light-Emitting Diodes With InxAl1-xAs Strain-Reducing Layers - Ruizhe Yao; Nicholas Weir; Chi-Sen Lee; Wei Guo (IEEE Photonics Journal)
In this paper, broadband InAs quantum-dot (QD) superluminescent light-emitting diodes (SLEDs) are grown by molecular beam epitaxy, fabricated, and then characterized. In order to achieve broadband and uniform emission spectra, the active regions contain a combination of chirped InAs QDs with different InxAl1-xAs strain-reducing layers (SRLs). It has been shown that the InxAl1-xAs SRLs can effectively enlarge the QD emission energy separation between the ground and the excited states. In this paper, QDs with increased energy separation are utilized to enable a broadband QD ensemble by adding additional QD layers with the ground state emission wavelength tuned to fill the gap in emission. In addition, we employed a short postgrowth annealing process of 30 s to further even out the emission spectra. Characterizations of the emission spectra of the as-grown QDs and fabricated QD SLEDs are performed by room-temperature photoluminescence and electroluminescence under continuous-wave (c-w) operation, respectively. In the SLED devices, a broad and uniform spectrum with a linewidth of 100 nm at 3 dB is realized at an injection current level of 100 mA, and no significant spectrum dip is observed in the entire injection current window ranging from 50 $μ\text{A}$ to 100 mA.